Ruminal metabolism, blood parameters and animal behavior of bulls submitted to sub-acute ruminal acidosis (SARA) receiving different buffers in high-concentrate diets (Acta Scientiarum. Animal Sciences, 2025)
This study aimed to evaluate the supplementation of four different buffers into a high-grain diet on ruminal fermentation, blood metabolites, and feeding behavior of feedlot cattle. Five rumen-cannulated bulls (492 ± 24 kg) were distributed in a 5 x 5 Latin square design, through the treatments: CONT (no buffer), RUMO, RUMF, BICA and ALGA. The buffers did not alter (p > 0.05) the apparent digestibility of nutrients, ruminal fluid pH, volatile fatty acid profile, and acetic/propionic ratio compared to the CONT. Except for propionic and isovaleric acids, which were different (p < 0.05) among treatments at 4 and zero hours after feeding, respectively. Ruminal lactic acid accumulation was greater (p < 0.05) in BICA, while ammoniacal nitrogen concentrations were highest (p < 0.05) in CONT and lowest in RUMF. Blood glucose and creatinine were unaffected (p > 0.05), whereas urea and lactate concentrations were reduced (p < 0.05) in RUMO. Among the enzymes, only gamma-glutamyl transferase and creatine kinase showed treatment effects (p < 0.05). Furthermore, feeding and drinking times were unaffected by treatments; however, rumination increased (p < 0.05) in BICA, and idleness was higher in CONT. Overall, buffer inclusion modified ruminal and metabolic responses, indicating a possible modulation of ruminal acidosis.